Online purchase experience and intention of Indonesian customers - , ELWIN MURSITO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Internet has developed into a new distribution channel and the evaluation of this channel. E-commerce has now identified. Using the Internet to shop online has become one of the primary reasons to use the Internet combined with searching for products and finding the information about them. With Internet, it gives customer control in access information on product and services. According to previous studies, consumersâ characteristics and goals have been found to influence their behaviors such as purchasing, revisiting intentions, and attitudes toward a website (Wu, 2003). In addition, consumer characteristics are of the factors affecting their behavior. This research looks at Indonesian online customers behavior, regarding their online and searching behavior that related to the intention in online purchase and actual online purchase. Data was collected by questionnaire that distributed directly and personally to the respondents.The study employed purposive and non probability sampling method. The hypothesised model is validated empirically using data collected from 390 people in Universitas Gadjah Mada (UGM) Campus as a state university and Atma Jaya Campus as a private university .The results showed that In online business should be honesty in the transaction between seller and buyer. With honesty, it will build a sense of trust that will impact to the commitment in the transaction (on time delivery, good packaging, and many more)